الولي في الزواج عند المذاهب الأربعة - Atifah Muhammad Sha’ari; عاطفة محمد شعاري (2022)
This research was included the meaning of wali, conditions, difference of waIi and importance of wali according to four schools. The purpose of this research was made to understand more and clear about the wali in the marriage, and in this research, problem relating wali was discussed, because some people today seeing unimportant to the issue of wali in the marriage. This problem always occurs when they have no wali or do not know arrange of wali according to hokum syara'. Although the explanation countenanced based on according to four schools, the writer emphasized more to "qaulumjih" that means, opinion of unanimous and countenance dalil from AI-Quran and Hadith to support arguments has been given.